A Note on Selected Names of Colorado Medical Marijuana Dispensaries. (3rd April 2017) - Nuessel, Frank
Abstract : This article offers information about the names of marijuana dispensaries in Colorado. First, it provides a brief overview of popular cultural references to the drug in film and music. Second, it considers its medical uses. Third, it examines legal issues related to its sale and use. Fourth, it reviews briefly the slang terminology for marijuana. Fifth, it discusses the notion of "dispensary." Sixth, it utilizes an existing database of 424 names for medical marijuana dispensaries in Colorado. Finally, it considers selected linguistic aspects of the names for marijuana dispensaries in Colorado.